Browning inhibition and lipid peroxidation change of fresh-cut romaine lettuce by arginine treatment - Nilprapruck, Phrutiya; Usaha, Thitiporn; Kaokaen, Tawinan (Science, Engineering and Health Studies, 2025)
This study aimed to assess the effect of sodium arginine on browning inhibition and lipid peroxidation in fresh-cut romaine lettuce kept for 15 days at 6±1 °C and 85% relative humidity. The experimental design was a completely randomized design with four treatments: The romaine lettuce was immersed in 0 (distilled water), 1 mM, 10 mM, and 20 mM arginine for 10 min. These results showed that the use of 20mM arginine can inhibit browning compared to other treatments. Reduced levels of phenolic compounds and phenylalanine ammonia lyase were linked to the suppression of browning in romaine lettuce, although polyphenol oxidase activity increased during storage. Additionally, there were studies on the change in lipid peroxidation, which is one of the causes of membrane deterioration. The result indicated that arginine can reduce the process of lipid peroxidation related to the decrease of lipoxygenase activity, malondialdehyde and hydrogen peroxide content compared with the control. The inhibition of stress tolerance by arginine could relate to its influence on metabolic pathways, cellular signaling, or oxidative stress. Arginine enhances stress tolerance, which leads to the production of polyamines that stabilize cell membranes and proteins, scavenge reactive oxygen species, and regulate ion channels, enhancing stress resilience. Hence, these results indicated that arginine treatment inhibited browning symptoms and membrane damage in the process of lipid peroxidation.